Pengaruh Ukuran Perusahaan dan Struktur Modal Terhadap Nilai Perusahaan Sektor Energi - Ravel Velicia Wijaya; Usnia Wati Keristin (MDP Student Conference, 2026)
This study aims to examine the effect of firm size and capital structure on firm value. The sample of this study consists of 58 companies selected through purposive sampling from a total of 91 energy sector companies listed on the Indonesia Stock Exchange during the 2022-2024 period. The data used are secondary data obtained from the companies’ annual reports published on the official website of the Indonesia Stock Exchange. The data were analyzed using linear regression with the assistance of SPSS version 23. The results of the study indicate that firm size and capital structure have no significant effect on firm value.